SOSIALISASI PENGETAHUAN BIDANG ADMINISTRASI PERKANTORAN BAGI SISWA SMK NU 01 BELIK - Muhammad Dede Puja Kusuma; Ardian Ridwanca (Abdi Jurnal Publikasi, 2026)
This outreach program aims to improve the understanding and skills of SMK NU 01 Belik students in office administration, particularly in facing the increasingly competitive demands of the workplace. The outreach program is motivated by the importance of mastering office administration knowledge as a basic competency for vocational school graduates in business and management. The program's implementation method involves interactively delivering material to students on office administration in the workplace, thus better preparing them to enter the workforce in various industries. The results of the program indicate an increase in student knowledge and motivation in understanding modern office administration concepts and practices, such as archives management, business communication, and digital document management. This program also strengthens the relationship between universities and vocational high schools in an effort to support the improvement of human resources who are work-ready and adaptable to developments in administrative technology.